Pengembangan Video Pembelajaran IPA Berbasis Doratoon dengan Model ADDIE bagi Siswa SMP - Nurwahyuni Mansyur; Syamsunir; Muhammad Takdir; Handy Ferdiansyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to produce a valid and practical Doratoon web-based science learning video media for eighth grade students at UPT SMP Negeri 2 Kulo. The background of this study is the low visualization of abstract science concepts, so it requires innovative media to help students' understanding. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data collection instruments include validation sheets for material experts and media experts, as well as response questionnaires for teachers and students to measure practicality. The results of the study showed that the Doratoon learning video media was declared